The Music Engagement Program for people with Alzheimer's disease and dementia: Pilot feasibility trial outcomes. (August 2021) - Gulliver, Amelia; Pike, Georgia; Banfield, Michelle; Morse, Alyssa R.; Katruss, Natasha; Valerius, Harley; Pescud, Melanie; McMaster, Mitchell; West, Susan
Highlights: Music Engagement Program (MEP) was highly acceptable to residents, staff, and family. The MEP improved depression and wellbeing for people with Alzheimer's and dementia. Workforce shortages and time constraints prevent delivery of these programs by staff. Abstract: Alzheimer's disease and dementia are common, highly disabling conditions frequently requiring residential care. This exploratory proof-of-concept study aimed to determine if the specialised Music Engagement Program (MEP) was sustainable, acceptable, and effective in improving quality of life, emotional wellbeing, and depression symptoms in this population. Sixteen residents, six staff members, and three family and community members took part in the evaluation of the MEP for people living with dementia in a residential aged-care nursing home in Canberra, Australia. Multiple methods were used. Quantitative evaluation assessed residents' depression symptoms (Cornell scale) at pre- and post-intervention, and emotional wellbeing pre- and post-session. Qualitative interviews with staff, and family and community members addressed the MEP's acceptability and potential sustainability. Results showed residents' mean depression scores were reduced from pre- to post-intervention ( p = .039; d z = 0.72). Interviews established multiple benefits for residents including improved mood, calmness, and reduced aggression. However, staff did not believe it was feasible to continue the MEP sessions beyond the trial period without an external facilitator, citing potential difficulties in adhering to internal activities due to time constraints. This pilot study provides encouraging preliminary evidence for the MEP's acceptability and potential effectiveness for improving depression and wellbeing in this group.